Treatment outcome of children with acute lymphoblastic leukaemia in HUSM - Nik Nasiruddin, Nik Leh (2007)
Introduction Acute lymphoblastic leukaemia is the most common malignant disease in children. There is neither national or international consensus about risk assignment, and no uniformed chemotherapy regime accepted. As a result, it is often difficult to compare the outcome from one group with another. In Hospital Universiti Sains Malaysia (HUSM), the children were treated using EORTC protocol. Other centers in Malaysia treat childhood ALL with different treatment protocol. There was only one formal study reported regarding the outcome of children with ALL in Malaysia. However none comparative study of the effectiveness of each treatment protocol carried in Malaysian population. This study was the first to analyse childhood ALL in HUSM. Objectives The main objective was to evaluate treatment outcome of children with ALL who received chemotherapy at Pediatric Oncology Unit in HUSM. The specific objective was to determine survival rate and risk factors for relapsed ALL and death among children with ALL treated with EORTC treatment protocol.Methodology The study was conducted at Pediatric Oncology Unit in HUSM. This was a retrospective study involving children with ALL who was diagnosed and treated between I sl January 1990 and 31 sl December 2003. Children aged I to 13 years and fulfilled the inclusion and exclusion criteria would be enroll in the study. Results There were a total of 138 children with diagnosis of ALL and received treatment at Pediatric Oncology Unit in HUSM from ISIJanuary 1990 to 31 s1 December 2003. A total of 102 children who fulfilled all inclusion and exclusion criteria were available for further review. The mean duration of follow-up was 93 months (SD 40). The minimum follow-up duration was 37 months and maximum duration was 186 months. Most of relapse occurred within 2 year after diagnosis. Only 2 cases of relapse occurred 5 years after diagnosis. Isolated BM relapse (22%) was the most common site of relapse. Overall EFS rate at 1, 3 and 5 years was 81.4% (SE ± 3.9), 59.8% (SE ± 4.9) and 55.3% (SE ± 5.0) respectively. Multiple Cox proportional analysis showed children aged, WBC count at diagnosis and early response to single prednisolone were the significant prognostic factors for the outcome of children with ALL. There was increased risk of poor outcome (relapse or death) in children aged at 10 to 13 years at about 4 times (95% CI 1.47; 10.44, p=0.006); 2.3 times (95% CI 1.09; 5.00, p=0.030) in children with WBC count at diagnosis more than 100.0 X103/!lL; and those poor early response to single prednisolone at about 2.6 times (95% CI 1.28; 5.20, p=0.008). Conclusion Survival in this was comparable to developing countries but study remained low compared to developed countries. Most of relapse occurred within 2 year after diagnosis with isolated BM relapse was being the most common site of relapse.